2013
DOI: 10.1080/10548408.2013.835227
|View full text |Cite
|
Sign up to set email alerts
|

Online travel purchasing: A literature review

Abstract: ABSTRACT. Over the past two decades, there has been an increasing focus on the development of Information and Communication Technologies (ICTs), as well as the impact that they have had on the tourism industry and on travelers' behaviors. However, research on what drives consumers to purchase travel online has typically been fragmented. In order to better understand consumers' behavior toward online travel purchasing, this article offers a review of articles that were published in leading tourism and hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 93 publications
2
63
0
7
Order By: Relevance
“…There is a lack of research regarding perceived trust in online shopping for tourism products and services (Amaro & Duarte, 2013;Kim, Chung, & Lee, 2011). Therefore, it is relevant to add trust since the few studies that have considered trust in online travel shopping have also produced mixed results.…”
Section: Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack of research regarding perceived trust in online shopping for tourism products and services (Amaro & Duarte, 2013;Kim, Chung, & Lee, 2011). Therefore, it is relevant to add trust since the few studies that have considered trust in online travel shopping have also produced mixed results.…”
Section: Trustmentioning
confidence: 99%
“…Knowing the driving forces that determine travellers' intentions to purchase travel online is paramount for the successful implementation of online marketing strategies (Lee, Qu, & Kim, 2007) and to convert potential customers to actual ones and retain them (Limayem, Khalifa, & Frini, 2000). Since prior research addressing online travel shopping has been typically fragmented and with contradictory results, it is important to further investigate this topic (Amaro & Duarte, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The technology which is easy to use in the adoption phase has positive influence on the consumer's attitude towards using it (Satama 2014). Effort expectancy has been strongly supported in case of online travel shopping adoption (Amaro and Duarte 2013). The following hypothesis is therefore proposed:…”
Section: Effort Expectancymentioning
confidence: 99%
“…Performance expectancy has proved to be a strong antecedent in consumer e-commerce travel adoption studies. Amaro and Duarte (2013) conducted a meta-analysis of online travel purchasing adoption research and found that performance expectancy was a significant variable. San Martin and Herrero (2012) applied UTAUT model in their study and established that Performance expectancy positively influences online travel purchase intentions.…”
Section: Performance Expectancymentioning
confidence: 99%
“…Electronic word-of-mouth have facilitated travel information searching behavior, and influenced tourists' travel planning behavior [8,9]. Tourists nowadays are increasingly using eWOM to inform themselves about travel-related services and products, for travel planning and travel related purchasing [10][11][12]. …”
mentioning
confidence: 99%